Exploratory Factor Analysis: Analysis of Islamic Bank Sustainability Factors in Facing the Disruption of the Industrial Revolution - Singgih Muheramtohadi; Choirul Huda; Retno Septia Adila (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
AbstractPurpose - In this study, researchers are interested in analyzing the factors of resilience (sustainability) that must exist or be carried out by Islamic banks to challenge the disruption of the industrial revolution 4.0.Method - This research is quantitative research. The research approach is exploratory which has the intention to obtain a description and understanding of the problems experienced by researchers. The instrument in this study was a questionnaire which was then tested for validity and reliability. After the data has been collected, the data is tested with the stages of testing confirmatory factor analysis data which is able to reduce a number of variables into several dominant factors that affect the sustainability of Islamic banks in facing the disruption of the industrial revolution 4.0.Result - This study concludes that: 1) 18 variables each have a Measure of Sampling Adequacy (MSA) value higher than 0.5 and are categorized as having met the adequacy of the sample. 2) Factor analysis is suitable for simplifying the group of 18 variables. 3) Two dominant factors are formed, which are called the customer's financial benefit factor and the customer's safety and comfort factor.Implication - This research helps Islamic banks to remain sustainable from the onslaught of the disruption of the Industrial revolution 4.0 based on the variables of customer desires.Originality - This study focuses more on Islamic banking instead of professional banking as in previous studies and in the analysis the researcher uses exploratory factor analysis to determine the dominant factor from series of variables. The study is different from previous research.